Aortic Root Enlargement by “Y” Technique – Our Experience (Cardiovascular Journal, 2024)
Aortic valve replacement is the commonest valvular surgery done around the world. In Asian population the aortic valve annulus size is smaller. So there is always a chance of patient prosthesis mismatch. There a number of techniques of aortic root enlargement during aortic valve replacement. We have used ‘Y incision technique’ in six of our patients in this case series. This technique is feasible and perioperative outcomes are promising. But it needs more mid and long - term results.Cardiovasc j 2024; 16(2): 98-101